Remodeling of the liver fibrosis microenvironment based on nilotinib-loaded multicatalytic nanozymes with boosted antifibrogenic activity - Jing, Huaqing; Ren, Yingzi; Zhou, Yue; Xu, Min; Krizkova, Sona; Heger, Zbynek; Lu, Qiang; Wang, Siyu; Liang, Xiaoyang; Adam, Vojtech; Li, Nan (Acta pharmaceutica Sinica. B, 2023)
Liver fibrosis is a reversible pathological process caused by chronic liver damage and a major risk factor for hepatocellular carcinoma (HCC). Hepatic stellate cell (HSC) activation is considered the main target for liver fibrosis therapy. However, the efficiency of this strategy is limited due to the complex microenvironment of liver fibrosis, including excessive extracellular matrix (ECM) deposition and hypoxia-induced imbalanced ECM metabolism. Herein, nilotinib (NIL)-loaded hyaluronic acid (HA)-coated Ag@Pt nanotriangular nanozymes (APNH NTs) were developed to inhibit HSCs activation and remodel the microenvironment of liver fibrosis. APNH NTs efficiently eliminated intrahepatic reactive oxygen species (ROS) due to their inherent superoxide dismutase (SOD) and catalase (CAT) activities, thereby downregulating the expression of NADPH oxidase-4 (NOX-4) and inhibiting HSCs activation. Simultaneously, the oxygen produced by the APNH NTs further alleviated the hypoxic microenvironment. Importantly, the released NIL promoted collagen depletion by suppressing the expression of tissue inhibitor of metalloproteinase-1 (TIMP-1), thus synergistically remodeling the microenvironment of liver fibrosis. Notably, an in vivo study in CCl4-induced mice revealed that APNH NTs exhibited significant antifibrogenic effects without obvious long-term toxicity. Taken together, the data from this work suggest that treatment with the synthesized APNH NTs provides an enlightening strategy for remodeling the microenvironment of liver fibrosis with boosted antifibrogenic activity.
Keywords: ECM; Liver fibrosis; HSCs; Hypoxia; Nilotinib; Nanozyme; Microenvironment remodeling; Collagen